Image Restoration Menggunakan Metode Lucy Richardson pada Citra Digital - Sammaditthi Gotama; I Wayan Santiyasa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
This journal discusses the use of the Lucy-Richardson method for image restoration on digital images. Digital images are often affected by noise or blur, which can cause the image to be too contrasted, out of focus, less sharp, and so on. Therefore, digital image processing technology is very important to improve image quality. Image restoration is one of the digital image processing techniques used to improve images that are affected by noise or blur. The Lucy-Richardson method is one of the methods that can be used to perform image restoration on digital images. In this journal, we will discuss the basic theory of the Lucy-Richardson method, the implementation of the Lucy-Richardson method on digital images, and the evaluation of the results of using the Lucy-Richardson method on digital images. The purpose of this journal is to provide a better understanding of the use of the Lucy-Richardson method for image restoration on digital images.